Undergraduate LIS Education in Pakistan: An Overview - Muhammad Ijaz Mairaj (Pakistan Journal of Information Management & Libraries, 2016)
The paper gives an account of undergraduate level library and information science education in Pakistan including independent certificate courses, an optional subject at intermediate and bachelor level, and bachelor program of Allama Iqbal Open University. The paper is based on the literature review and personal communications with selected professionals. There appeared gap in local literature regarding contemporary state of undergrad level education. The review of literature and senior professionals suggested that radical changes are necessary in policies, programs and curricula of different programs at undergraduate level to raise the quality of education.